The state of the agri-, food-, and climate-tech innovation ecosystem in Morocco: Country report - Roberto, Viton; Garzaron, Lucia; Menza, Gianpiero; Mounir, Aya; Zaccari, Claudia; Dolinga, Moritz (2025)
Morocco boasts a rich agricultural heritage, with around 68 percent of its land dedicated to agriculture. The sector contributes around 10.1 percent to the country's GDP, and 35 percent of its population lives in rural areas. In 2008, the agricultural sector underwent a transformation with the launch of the Green Morocco Plan, aimed at boosting productivity, competitiveness, and resilience to climate change. Building on this foundation, the Generation Green 2020-2030 strategy presents a new vision for further development.